(untitled) (Journal of Science and Technology, 2024)
In this research work, snail meat was canned. Microbial and proximate analyses of fresh and canned snail meat were carried out. The purpose was to investigate the effects of brine, vinegar, and combinations of different concentrations of brine and vinegar on the microbial counts and proximate composition, aimed at establishing the appropriate method of blanching during canning. The snail meat was blanched with different concentrations of brine of 1%, 3% and 5%; vinegar concentrations of 50%, 75% and 100%; and a mixture of 3% brine + 50% vinegar, 3% brine + 75% vinegar, 5% brine + 75% vinegar and 5% brine + 100% vinegar. The initial number of microorganisms in the treated samples after blanching determines the efficiency of the chemical preservative based on their viable count. The result showed both 1% brine and 3% brine concentrations had 20% and 28% percentage reductions in microbes of the snail meat respectively by the end of the first day. However, there was a progressive increase in the total viable count after the first day until the projected 7th day. 5% brine recorded a 51.57% reduction and was more effective in reducing viable organisms of the sample for the first two days but also increased progressively until the seventh day. The 50% vinegar concentration showed a higher viable count at the end of the seven days of test with a 57.89% reduction in the viable count. The 75% vinegar was also effective, with a 60.53% reduction in the viable count, and 100% vinegar, with a 68.4% reduction, as the best. It was evident from this study that the optimum brine concentration of 5% can be established as brine media concentration according to its high microbial reduction ability and lowest pH of 5.9.